2010
DOI: 10.1590/s1679-45082010ao1464
|View full text |Cite
|
Sign up to set email alerts
|

Assessing knowledge of Medical undergraduate students on palliative care in end-stage disease patients

Abstract: Medical students that will conclude the undergraduate course are aware of the nature and the importance of palliative care, even when they have no previous experience during training at university.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…The data corroborate the research by Oliveira and collaborators 45 , in which almost all respondents said that they provide emotional support to patients (90%) and talk about the pathology, informing those in the terminal phase of the actual diagnosis (70%). Regarding palliative care, Barclay and collaborators 49 verified 2015 the knowledge of such care by medical students; and Moraes and Kairalla 50 , in a 2010 article, identified that graduating students are aware of the importance of palliative treatment, even without facing this experience during their academic life, which is confirmed by the present work.…”
Section: Resultssupporting
confidence: 77%
“…The data corroborate the research by Oliveira and collaborators 45 , in which almost all respondents said that they provide emotional support to patients (90%) and talk about the pathology, informing those in the terminal phase of the actual diagnosis (70%). Regarding palliative care, Barclay and collaborators 49 verified 2015 the knowledge of such care by medical students; and Moraes and Kairalla 50 , in a 2010 article, identified that graduating students are aware of the importance of palliative treatment, even without facing this experience during their academic life, which is confirmed by the present work.…”
Section: Resultssupporting
confidence: 77%